2011
DOI: 10.1016/j.ajpath.2011.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Mu Opioid Signaling Protects Against Acute Murine Intestinal Injury in a Manner Involving Stat3 Signaling

Abstract: Opiates have long been used as analgesics to relieve pain associated with various medical conditions. Here, we evaluated the effect and mechanism of mu opioid signaling on the intestinal wound healing response and assessed downstream pathways known to be protective against intestinal injury. Mice (C57BL/6) were exposed to 3% dextran sodium sulfate (DSS) for 7 days or 4% DSS for 5 days followed by 7 days of water. The mu opioid receptor (MOR)-specific agonist [D-Arg2,Lys4]dermorphin-(1,4)-amide (DALDA) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 54 publications
3
38
0
Order By: Relevance
“…Our data on wound closure are in agreement with earlier observations on the contribution of MOPr and DOPr in wound healing process. 5,6,17,21 Healing of punch biopsy cutaneous wounds, burn wounds and cage fight wounds was demonstrated to be delayed in DOPr-KO mice. 22 Delayed wound healing in DOPr-KO is accompanied by an aberrant epithelial phenotype with an atrophic epidermal layer and hypertrophic wound edges.…”
Section: Discussionmentioning
confidence: 99%
“…Our data on wound closure are in agreement with earlier observations on the contribution of MOPr and DOPr in wound healing process. 5,6,17,21 Healing of punch biopsy cutaneous wounds, burn wounds and cage fight wounds was demonstrated to be delayed in DOPr-KO mice. 22 Delayed wound healing in DOPr-KO is accompanied by an aberrant epithelial phenotype with an atrophic epidermal layer and hypertrophic wound edges.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, pharmaceutical efforts have focused on targeting STAT3-activating kinases or inhibitors. As elevated STAT3 activity have been reported in IECs of patients with IBD, a study by Goldsmith et al [127] revealed that DSS-induced colitis is protected by treatment with a specific mu opioid receptor agonist, called DALDA, by promoting proliferation and migration of IECs in a Stat3 activation-dependent manner. Furthermore, a recent in vitro and in vivo study has shown that Stat1-mediated Th1 and Stat3-dependent Th17 proinflammatory responses in DSS-induced colitis were inhibited by icariin, a bioactive compound from plants in Epimedium family [128].…”
Section: Jak/stat Signaling In Iecs and Myeloid Cellsmentioning
confidence: 96%
“…Occult bleeding was evaluated 4 days after administration of DSS or water control (Hemoccult; Beckmann Coulter Inc., Fullerton, CA, USA), in accordance with internal pilot studies that showed occult bleeding to be reliably observable in this model from day 4 onwards. Clinical score, assessing weight loss, occult blood and stool consistency were calculated as previously described (Goldsmith et al, 2011). Mice were killed at the indicated time points by CO 2 asphyxiation followed by cervical separation.…”
Section: Dss-induced Acute Injury and Histological Evaluationmentioning
confidence: 99%
“…The colon was dissected and flushed with ice-cold phosphate-buffered saline, longitudinally splayed, swiss rolled, fixed in 10% formalin for 24 h, and then embedded in paraffin. Colitis severity was evaluated using Hematoxylin-Eosin-stained sections by a blinded investigator on a scale from 0 to 40, as described previously (Goldsmith et al, 2011).…”
Section: Dss-induced Acute Injury and Histological Evaluationmentioning
confidence: 99%